2015
DOI: 10.1007/s12088-015-0523-y
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Direct-Current Electric Field on Enzymatic Activity and the Concentration of Laccase

Abstract: This work investigates the effect of directcurrent electric field on the extracellular enzymatic activity, concentration and other experimental parameters of laccase from Trametes versicolor. The results showed that laccase could significantly contribute to the change of pH at the end of graphite electrode. In addition, it increased the electrical conductivity of the water. In the experiment, the optimum pH and catalytic pH range for laccase activity were 3.0 and pH 2.5-4.0. The application of 6 V direct curre… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 32 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…Moreover, a similar study reported that a direct electric current exhibited less effect on the laccase enzyme, and the laccase and electric field exhibited a better response to practical environment changes. 28…”
Section: Resultsmentioning
confidence: 99%
“…Moreover, a similar study reported that a direct electric current exhibited less effect on the laccase enzyme, and the laccase and electric field exhibited a better response to practical environment changes. 28…”
Section: Resultsmentioning
confidence: 99%
“…Owing to the hydroxyl group in its structure, phenol exhibits weak acidity. However, it has been demonstrated that laccase exhibits higher catalytic activity in acidic environments [4]. This property makes laccase a good candidate for promoting the catalytic degradation of phenol.…”
Section: Resultsmentioning
confidence: 99%
“…Hence, laccase is considered an environmentally friendly fermenting agent, and its role in biodegradation catalysis has been extensively studied [3]. Previously, the effects of electric fields on white rot fungi and laccase, as well as the effects of electric fields on the biodegradation of phenolic compounds were studied [4]. Nevertheless, few studies have reported the effects of electric fields on phenol biodegradation catalyzed by laccase.…”
Section: Introductionmentioning
confidence: 99%
“…13 Bani-Melhem et al found that integrating the electrocoagulation process with a membrane bioreactor was an effective method for wastewater treatment and for improving membrane filtration. 14 Some researchers studied that external electric fields were capable of enhancing the activities of enzymes and anammox bacteria, 15,16 Additionally, previous studies indicated that a bio-electrocoagulation system with Fe-C electrodes was able to increase the biomass and system performance. 17,18 These results revealed that electrocoagulation technology was able to increase membrane filtration performance as well as activated sludge performance.…”
Section: Introductionmentioning
confidence: 99%